Self-Concept and Self-Esteem, Determinants of Greater Life Satisfaction in Mountain and Climbing Technicians and Athletes - Laura Martín-Talavera; Óscar Gavín-Chocano; Guillermo Sanz-Junoy; David Molero (MDPI AG, 2023)
In recent decades, the exponential growth that sports practice in mountain and climbing disciplines have experienced has led to trying to find an explanation for the predisposition of those socio-emotional factors of these athletes that are considered in the search for sensations and the achievement of greater satisfaction with life. In this study, 4818 people with a sports license in the Spanish Federation of Mountain and Climbing Sports (FEDME) participated; 67.1% were men and 32.9% women. The mean age of the participants was 49.42 years (±11.9), between a range of 18 to 76 years. The following instruments were used: the Self-concept scale (AF5), the Rosenberg Self-esteem Questionnaire and the Life satisfaction scale (SWLS). The objective of this research was to study the enhancing effect of self-esteem between self-concept (physical, emotional and social) and life satisfaction. A reflective model of structural equations (PLS-SEM) was applied based on the proposed theoretical framework from an explanatory-predictive perspective. The results show the self-esteem determination coefficients [(Q2 = 0.141); (R2 = 0.302)] and life satisfaction [(Q2 = 0.243); (R2 = 0.342)] in the estimation of the model, indicating an adequate fit. Mountaineering and climbing sports can be very rewarding, but they can also be challenging and frustrating. Having a good self-concept and good self-esteem allows the athlete to enjoy achieving greater life satisfaction.